Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-12-14T12:50:36+01:00
√1i 9/16 * (-2)do kwadratu + 1,2 * 5/12 = 1 3/4*4+ 12/10*5/12=
7/4*4 + 1/2=7+1/2=14/2+1/2=15/2=7i1/2
2009-12-14T12:53:53+01:00
√1i 9/16 * (-2)do kwadratu + 1,2 * 5/12=√25/16*4+12/10*5/12=5/4*4+60/120=
=20/4+1/2=5+0,5=5,5
2009-12-14T12:54:30+01:00
√1i 9/16 * (-2)do kwadratu + 1,2 * 5/12=

√25/16 * (-2) do kwadratu + 6/5 * 5/12=
5/4* (-2)do kwadratu + 2,88=
(4/5)²+2,88= 16/25+2,88=0,64+2,88=3,52

MAM NADZIEJĘ, ŻE NIC NIE POMYLIŁAM.
POZDRAWIAM :)